Factors of IT Project Failure: A Literature Review - Betantiyo Prayatna; Muhamad Ihsan Suzeta; Honaris Clausa (Technologia Journal, 2025)
This study aims to identify the key factors contributing to IT project failure. A literature review serves as the primary research method, with articles sourced from leading journal databases such as Scopus, IEEE Xplore, Google Scholar, and ProQuest using the keyword "IT project failure factors." The findings reveal that IT project failure is primarily caused by individual, organizational, and technical factors. Specific factors identified include a lack of project management skills, poor communication among team members, inadequate planning, and constraints related to budget and technology. Individual factors involve insufficient expertise and leadership, while organizational factors include weak support from management and unclear project objectives. Technical factors, such as outdated systems and integration issues, also play a significant role. This study emphasizes the need for a holistic approach in IT project management to minimize failure risks. Effective project planning, strong leadership, clear communication, and adequate resource allocation are crucial in ensuring success. By understanding these failure factors, organizations can implement better strategies to enhance project outcomes. Future research could explore specific mitigation strategies and best practices to address these challenges, providing valuable insights for IT professionals and project managers in improving project success rates.